Stereoisomer separation of flavanones and flavanone-7-O-glycosides by means of nanoliquid chromatography employing derivatized β-cyclodextrins as mobile-phase additive - Zátopková, Renata; Aturki, Zeineb; Bednář, Petr (Journal of separation science, 2020)
A nanoliquid chromatographic method for the stereoisomer separation of some flavanone aglycones and 7-O-glycosides has been proposed employing a C18 capillary column and a chiral mobile-phase additive such as cyclodextrin. The chiral separation of eriodictyol, naringenin, and hesperitin was obtained by addition of carboxymethyl-β-cyclodextrin to the mobile phase, whereas eriocitrin, naringin, narirutin, and hesperidin diastereoisomers were resolved by using sulfobutyl ether-β-cyclodextrin. The influence of the composition of the mobile phase, the length of the capillary column, and the flow rate on the chiral recognition were investigated. At optimum conditions, baseline separation for the selected aglycones and glycosylated forms were achieved with a mobile phase consisting of 50 mM sodium acetate buffer pH 3 and 30% methanol containing 20 mM of carboxymethyl-β-cyclodextrin and 10 mM of sulfobutyl ether-β-cyclodextrin, respectively. Precision, linearity, and sensitivity of the method were tested. Limits of detection and quantification for the studied flavanone glycosides were in the range 1.3-2.5 and 7.5-12.5 µg/mL, respectively. The method was used for the determination of the diastereomeric composition of the flavanone-7-O-glycosides in Citrus juices after solid-phase extraction procedure.
Keywords: citrus juices; cyclodextrins; beta-Cyclodextrins; flavanony; stereoisomer separation; glykosidy; Stereoisomerism; nanotechnologie; Glycosides; Chromatography, High Pressure Liquid; Nanotechnology; vysokoúčinná kapalinová chromatografie; chiral mobile phase additive; stereoizomerie; Flavanones; beta-cyklodextriny; molekulární struktura; nano-liquid chromatography; Molecular Structure